Product-Service Systems Perspective for Framework Development for Assessing and Measuring System Maturity, System Readiness and Capability Readiness using Architecure Frameworks - Tetlay, Abideen (ICMR 2010 with permission, 2010)
This study investigates the use of Product-Service Systems (PSS) perspective for refinement of the Conceptual Framework for Assessing and Measuring System Maturity, System Readiness and Capability Readiness using Ar-chitecture Frameworks. Metrics and measurement frameworks have no meaning if they are not used to make deci-sions. The importance of decision making at the architectural level is particularly pertinent for System Maturity
Keywords: Product-Service Systems; Framework Assessment; System Maturity; System Readiness; Capability Readiness; Architecture Framework